2016
DOI: 10.1097/md.0000000000003573
|View full text |Cite
|
Sign up to set email alerts
|

Recommended Initial Antimicrobial Therapy for Emphysematous Pyelonephritis

Abstract: The aim of this study was to investigate the profiles of pathogens and patterns of antibiotic resistance of emphysematous pyelonephritis (EPN), offering recommendations for initial antibiotic treatment.Between January, 2001, and November, 2014, demographic data, presenting clinical features, management strategies, and treatment outcomes of 51 patients with EPN were retrospectively reviewed, analyzing microbiological characteristics of causative pathogens and patterns of antibiotic resistance.Overall survival r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 24 publications
1
17
0
3
Order By: Relevance
“…The most specific sign but rare is the perception of a subcutaneous crepitus facing kidney signifying the presence of gas, it is only present in 14% of cases. The causative organism is usually Escherichia coli (60% of cases) but Klebsiella pneumoniae was found in 25% of cases , sometimes Pseudomonas or Proteus mirabilis and vulgaris were found[5] [8]. The germ found in our case is Klebsiella pneumoniae ESBL.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…The most specific sign but rare is the perception of a subcutaneous crepitus facing kidney signifying the presence of gas, it is only present in 14% of cases. The causative organism is usually Escherichia coli (60% of cases) but Klebsiella pneumoniae was found in 25% of cases , sometimes Pseudomonas or Proteus mirabilis and vulgaris were found[5] [8]. The germ found in our case is Klebsiella pneumoniae ESBL.…”
mentioning
confidence: 74%
“…Over the last two decades, the implementation of PCD techniques facilitates maximum nephron sparing and restoration of renal function. Percutaneous drainage, rather, is now the gold standard of care and definitive management for the majority of patients with EPN [1] [5]. In the world, after the publication of the first case of EPN by Kelly et al in 1898 [6], EPN is currently limited to case series reported [5] [7] [8] [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that conservative management with initial fluid resuscitation and broad-spectrum antibiotics and later antibiotic treatment based on culture is successful. Lu et al have reported third-generation cephalosporins as the recommended initial drug in their patients with EPN and carbapenem in patients with prior hospitalization or antibiotic use; patients needing emergency hemodialysis or developing disseminated intravascular coagulation [ 20 ]. In our patients, we observed that the bacteria were sensitive to piperacillin-tazobactam and meropenem in most patients, while they were resistant to gentamicin and levofloxacin in many patients.…”
Section: Discussionmentioning
confidence: 99%
“…The single-agent options effective against EPN are at least third-generation cephalosporins and carbapenems. For high-risk patients, the combination of amikacin and third-generation cephalosporin is an option [ 11 ]. In this case, report, we highlighted that the clinical and imaging features of EPN may be helpful for physicians to diagnose EPN early, and to provide timely medical and surgical intervention for better outcomes.…”
Section: Discussionmentioning
confidence: 99%